PENEGAKAN HUKUM ADMINISTRASI LINGKUNGAN HIDUP TERHADAP PENCEMARAN PEMBUANGAN LIMBAH KULIT - Abdul Ropik Fauzi; Wahyu Nugroho; Fahririn Fahririn (JOURNAL IURIS SCIENTIA, 2023)
Enforcement of environmental administrative law is something that is often found in every environmental problem in cases of environmental pollution by industry. Administrative law enforcement is considered the most important law enforcement effort. This is because administrative law enforcement is more aimed at efforts to prevent pollution and environmental damage. The research method used is an empirical legal research method that is descriptive in nature using a normative juridical approach. The source of this research is primary data obtained through interviews as well as secondary data, namely laws and regulations related to the object of research. The research results obtained are first, the enforcement of environmental law due to violations of environmental pollution due to waste disposal by the leather tanning industry in Garut Regency based on Legislation in the Environmental Sector is not optimal and the supervisory function is weak, resulting in various violations by the leather tanning industry is still found; and second, several factors in enforcing environmental law in Garut Regency towards the leather tanning industry for waste pollution, namely internal factors and external factors.